MANAJEMEN KONFLIK TAPAL BATAS KAMPAR PEKANBARU (STUDI KASUS KECAMATAN BUKITRAYA PEKANBARU) - Destry Yani Rizki; Tuti Khairani Harahap (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Conflict Management Boundary between Pekanbaru District of Kampar (Case Study Sub-District of Bukitraya Pekanbaru) is an effort to resolve conflicts conducted by related parties in this case RW 15, RW 16 and RW 18 Simpang Tiga village Bukitraya sub-district to get a solution of the clarity of their status in administrative demography. This conflict management effort has been done since December 2015 until now and has not yet got the solution. According to Wirawan's theory, conflict management consists of third parties (conflict parties), conflict strategies, conflict control, and conflict resolution.This study aims to find out how the Conflict Management of the Boundary of Kampar Pekanbaru (Case Study Sub-District Bukitraya Pekanbaru) by using descriptive qualitative method where the author uses interviewing and observation techniques in the field with research informant, Sub-section Head of the Inter-Regional Border of Riau Province, Secretary of Lurah Simpang Tiga, Chairman of RW 15, RW 16, RW 18 Simpang Tiga Village and residents of RW 15, RW 16, and RW 18 Simpang Tiga Village.The result of the research shows that the management of boundary conflict in Kampar Pekanbaru (Case Study of Sub-district of Bukitraya Pekanbaru) has not been maximal since all the efforts are only done by RW 15, RW 16, and RW 18, people who feel disadvantaged. The factors that influence the management of Boundary Conflict Kampar Pekanbaru (Case Study Sub-District Bukitraya Pekanbaru) is the absence of commitment Pekanbaru City Government in enforcing the Minister of Home Affairs Regulation No. 18 of 2015 about the Boundaries of Kampar Regency with Pekanbaru City Riau Province and absence of supervision during the settlement of this conflict.Keywords: Conflict Management, Boundaries